(untitled) (Journal of International Studies, 2015)
Бүс нутгийн бүсшил болон даяаршлын талаар судлаачид ямар байр суурьтай байдаг мөн эдгээр хоёр үйл явцын нийтлэг болон ялгаатай шинж чанаруудыг авч үзлээ. Is Regionalization A Part of Globalization or an Alternative to It? Abstract: This article deals with the regionalization and the globalization, researchers points of view concerning these two terms and tries to find out common and different features of these two processes.